2005
DOI: 10.1200/jco.2005.23.16_suppl.6729
|View full text |Cite
|
Sign up to set email alerts
|

Experience with multiple myeloma in a public referral hospital in Nairobi, Kenya

Abstract: Multiple myeloma is a clonal malignant proliferation of the plasma cell line in terminal stages of immunological maturation of the B cell lineage. It has a male-to-female ratio of 2/1 and affects mainly the middle aged and elderly. It has not been characterized comprehensively locally. Methods: We retrospectively studied records of patients seen at the Kenyatta National Hospital, Nairobi between January 1994 and January 2004 inclusive. Information sought included demographic, clinical, radiologic, haematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Nearly one-third of patients were 50 years of age or younger, an observation that has also been noted by Odunukwe et al in Nigeria 16. Seven percent of patients were 40 years or younger, which is consistent with other reports from elsewhere in Africa,14,16,19 but twice as many as reported for Caucasians. Since this observation could be biased by the lower life expectancy in Africans, adjusting the incidence for age would allow for more reliable comparison.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nearly one-third of patients were 50 years of age or younger, an observation that has also been noted by Odunukwe et al in Nigeria 16. Seven percent of patients were 40 years or younger, which is consistent with other reports from elsewhere in Africa,14,16,19 but twice as many as reported for Caucasians. Since this observation could be biased by the lower life expectancy in Africans, adjusting the incidence for age would allow for more reliable comparison.…”
Section: Discussionsupporting
confidence: 91%
“…With a high prevalence of bone pain in the study population, it is likely that many of the patients in Ghana would have been prescribed NSAIDs by the time of referral, which could contribute to the development of renal impairment. One third of patients had hypercalcaemia, similar to a report from Kenya,11 however there is a wide variation (6.8–69%)in the prevalence of hypercalcaemia in Africans at diagnosis 12,13,19. Lytic lesions were more often detected on skull imaging, a reflection of the local protocol for investigating suspected myeloma.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The median age at diagnosis reported in this and other sub-Saharan Africa studies ranging from 53 to 62 years was closer to that reported for the African American population (65 years) and lower than that reported for White patients (71 years). 10 , 11 , 15 - 17 It appears that sub-Saharan Africans are at risk of early onset MM, a characteristic that has been confirmed in the African American population. 17 …”
Section: Discussionmentioning
confidence: 87%